Acute dose-dependent effects of lysergic acid diethylamide in a double-blind placebo-controlled study in healthy subjects - Holze, Friederike; Vizeli, Patrick; Ley, Laura; Müller, Felix; Dolder, Patrick; Stocker, Melanie; Duthaler, Urs; Varghese, Nimmy; Eckert, Anne; Borgwardt, Stefan; Liechti, Matthias E. (Neuropsychopharmacology (New York, N.Y.), 2021)
Growing interest has been seen in using lysergic acid diethylamide (LSD) in psychiatric research and therapy. However, no modern studies have evaluated subjective and autonomic effects of different and pharmaceutically well-defined doses of LSD. We used a double-blind, randomized, placebo-controlled, crossover design in 16 healthy subjects (eight women, eight men) who underwent six 25 h sessions and received placebo, LSD (25, 50, 100, and 200 µg), and 200 µg LSD 1 h after administration of the serotonin 5-hydroxytryptamine-2A (5-HT 2A ) receptor antagonist ketanserin (40 mg). Test days were separated by at least 10 days. Outcome measures included self-rating scales that evaluated subjective effects, autonomic effects, adverse effects, plasma brain-derived neurotrophic factor levels, and pharmacokinetics up to 24 h. The pharmacokinetic-subjective response relationship was evaluated. LSD showed dose-proportional pharmacokinetics and first-order elimination and dose-dependently induced subjective responses starting at the 25 µg dose. A ceiling effect was observed for good drug effects at 100 µg. The 200 µg dose of LSD induced greater ego dissolution than the 100 µg dose and induced significant anxiety. The average duration of subjective effects increased from 6.7 to 11 h with increasing doses of 25–200 µg. LSD moderately increased blood pressure and heart rate. Ketanserin effectively prevented the response to 200 µg LSD. The LSD dose–response curve showed a ceiling effect for subjective good effects, and ego dissolution and anxiety increased further at a dose above 100 µg. These results may assist with dose finding for future LSD research. The full psychedelic effects of LSD are primarily mediated by serotonin 5-HT 2A receptor activation.